2009
DOI: 10.1177/1038411108099291
|View full text |Cite
|
Sign up to set email alerts
|

The different variables that affect older males' and females' intentions to continue working

Abstract: This paper examined the impact of certain work-related factors on older workers" intentions to continue paid work and whether the impact of these work-related factors varies between men and women. Data were collected through a questionnaire survey of a sample of employees, aged 50 years and older, working in a large public sector organisation in Australia. Results identified the work-related factors that influence older workers" intentions to continue paid work as "importance of work", flexibility"and "interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 48 publications
6
79
0
6
Order By: Relevance
“…They concluded that 'in particular, meaningful work increases motivation among men and work ability increases motivation among women.' Likewise, 'importance of work' was found in an Australian study by Shacklock et al (2009) to be a significant factor influencing men's, but not women's intention to continue working. Our finding that job satisfaction was a significant factor also among women could reflect conditions specific to a university organization, but possibly also other attitudes held by Swedish women, compared to Germany and Australia.…”
Section: Gender and Views On Retirementmentioning
confidence: 95%
“…They concluded that 'in particular, meaningful work increases motivation among men and work ability increases motivation among women.' Likewise, 'importance of work' was found in an Australian study by Shacklock et al (2009) to be a significant factor influencing men's, but not women's intention to continue working. Our finding that job satisfaction was a significant factor also among women could reflect conditions specific to a university organization, but possibly also other attitudes held by Swedish women, compared to Germany and Australia.…”
Section: Gender and Views On Retirementmentioning
confidence: 95%
“…Workers who do not have a sense of job satisfaction will be in disequilibrium in terms of their worklife balance. Multiple studies have identified consistency in the levels of work-life balance and individuals' job satisfaction [34][35][36][37]. Such data indicated that further research into whether job satisfaction is a predictor of work-life balance for members of particular professions (e.g., mental health) would be beneficial.…”
Section: Variables Impacting Work-life Balancementioning
confidence: 99%
“…Organizational commitment involves individual employees' psychological attachment to the organization for which they work and therefore is a strong indicator of performance in the workplace [36]. There are multiple components of organizational commitment, reflecting various theories and beliefs surrounding the construct, which are discussed later in this proposal.…”
Section: Variables Impacting Work-life Balancementioning
confidence: 99%
“…It is rooted in environmental factors, such as job characteristics (see Brusch & Büsch, 2012) or marital life and personal factors such as physical well-being, financial and skills status (Beehr, 1986;Shacklock, Brunetto, & Nelson, 2009). Indeed, there is evidence that those motivated to work longer years can be broadly separated into two groups, those who need to work longer due to financial needs and those who enjoy their work so much that they do not wish to stop (at least not completely, see McNair, 2006).…”
Section: Outcomes Of Continuing Training Motivationmentioning
confidence: 99%